Lepto-hadronic model for the broadband emission of Cygnus X-1 - Pepe, Carolina (2015)
Context. Cygnus X-1 is a well-observed microquasar. Broadband observations at all wavelengths have been collected over the years.The origin of the MeV tail observed with COMPTEL and INTEGRAL is still under debate and it has mostly been attributed to thecorona, although its high degree of polarization suggests that it is synchrotron radiation from a jet. The origin of the transient emissionabove ∼100 GeV is also unclear.Aims. We aim to clarify the origin of the broadband spectral energy distribution (SED) of Cygnus X-1, focusing particularly on thegamma-ray emission, and to gain information on the physical conditions inside the jets.Methods. We developed a lepto-hadronic, inhomogeneous jet model and applied it to the non-thermal SED of Cygnus X-1. Wecalculated the contributions to the SED of both protons and electrons accelerated in an extended region of the jet. We also estimatedthe radiation of charged secondaries produced in hadronic interactions through several radiative processes. Absorption effects wereconsidered. We produced synthetic maps of the jets at radio wavelengths.Results. We find two sets of model parameters that lead to good fits of the SED. One of the models fits all the observations, includingthe MeV tail. This model also predicts hadronic gamma-ray emission slightly below the current upper limits. The flux predicted at8.4 GHz is in agreement with the observations available in the literature, although the synthetic source is more compact than theimaged radio jet.Conclusions. Our results show that the MeV emission in Cygnus X-1 may be jet synchrotron radiation. This depends mainly on thestrength of the jet magnetic field and the location of the injection region of the relativistic particles. Our calculations show that theremust be energetic electrons in the jets quite far from the black hole.